FENOMENA JIMAT AYAT AL-QUR’AN DALAM MASYARAKAT BARUS, TAPANULI TENGAH - Widiyanto, Rudi (An Natiq, 2024)
This study discusses the use of Quranic verses as amulets in Barus City, Tapteng Regency. This study was conducted using a qualitative method and a phenomenological approach. The findings of the study indicate that the Barus community uses Quranic verses as a dedication for protection and spiritual benefits. The amulets are usually in the form of Surah Al-Fatihah, the Throne verse, At-Talaq, Al-Falaq, Al-Ikhlas, and An-Nas. This study aims to explore the understanding of this phenomenon. This article discusses the function of amulets. Quranic verses are used in people's daily lives. These verses are used as a medium to increase faith, provide psychological strength, and invite good luck. The verses used by the community also vary in terms of meaning and form. According to the community's view, Quranic verses can also be objects that attract sustenance and can repel evil jinns and devils.